2015
DOI: 10.1007/s11270-015-2589-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Phenanthrene and Its Nitrogen Polycyclic Aromatic Hydrocarbon Analogues in Ageing Soil

Abstract: The impacts of phenanthrene and its nitrogen-containing analogues (N-PAHs) on seedling emergence and plant biomass of two terrestrial plant species, Lactuca sativa (lettuce) and Lolium perenne (rye grass), were investigated in soil over a 21-day exposure period. The data over 0-90-day soil-chemical contact time revealed that seedling emergence and plant biomass were significantly affected by N-PAHs even at the lowest concentration of 10 mg/kg. N-PAH amended soils showed greater inhibitory effects on seedling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…From the results, it can be seen that increased soil-contaminant-contact time showed removal of chemicals as well as reductions in the extraction of the remaining chemicals in soil; this may be due to volatilization, sorption and/or biodegradation (Welp and Brümmer 1999 ; Semple et al 2003 ; Anyanwu and Semple 2015b ). In soil for example, organic contaminants are known to undergo irreversible sorption.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the results, it can be seen that increased soil-contaminant-contact time showed removal of chemicals as well as reductions in the extraction of the remaining chemicals in soil; this may be due to volatilization, sorption and/or biodegradation (Welp and Brümmer 1999 ; Semple et al 2003 ; Anyanwu and Semple 2015b ). In soil for example, organic contaminants are known to undergo irreversible sorption.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Welp and Brümmer ( 1999 ) reported that a decrease in the bioavailability/extractability of organic contaminants is mostly due to sorption. In addition, biodegradative processes are known to contribute to loss (Towell et al 2010 ; Anyanwu and Semple 2015b ). Irrespective of the low concentrations measured, the inhibitory and/or stress effects on soil indigenous microbes were still obvious.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations